Analysis The Communication Skills of Children 2 Years Old Through Playing and Singing - Siti Rakiyah (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2020)
Playing and singing are central to children’s learning and development. When children play and sing, they give lots of different ways and times to learn for them. Playing and singing can support children’s learning and emotional development. How a good playing and singing could help children in speaking. This paper begins by looking at why playing and singing can be considered valuable pedagogical tool and in this paper also would discuss and analyze how playing and singing can help children 2 years old to improve the children speaking. Finally, this paper aims to explore how playing and singing can improve children’s speaking.